THE INFLUENCE OF PERCEIVED JUSTICE IN SERVICE RECOVERY ON COMPLAINANT SATISFACTION AND WORD-OF-MOUTH INTENTION AT HOTEL IN JAKARTA - Murni Setyawati (Jurnal Ilmiah Ekonomi Bisnis, 2019)
The purpose of this study is to assess the relative influences of distributive (DJ), procedural (PJ), and interactional (IJ) justices on customer satisfaction with service recovery and to examine the relationship between recovery satisfaction and word-of-mouth intention. On-site surveys were administered to collect data from hotel guests who stayed, and experienced a service failure at five-star hotels. The effects of procedural and interactional justice have a positive relationship with complainant satisfaction and word-of mouth intention. The results also confirmed the role of complainant satisfaction on word-of-mouth intention. Managerial implications of these findings are briefly discussed.